Analasis pengaruh instagram terhadap purchase intention melalui brand awareness dan brand trust pada starbucks surabaya - Ellitan, Lena; Rosari, Andriano De; Kristanti, Maria Mia (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of Instagram on Purchase Intention through Brand Awareness and Brand Trust on Starbucks Surabaya consumers. The sampling technique used is non-probability sampling by distributing questionnaires. The sample used in this study were 150 respondents. The requirements of the respondents in this study were domiciled in Surabaya, aged at least 18 years, visited the Starbucks Indonesia Instagram account for at least the last 3 months and were loyal customers who consumed at least 3 times in the last 3 months. The data analysis technique used is SEM-PLS analysis using the SmartPLS 3.0 program. The results of this study indicate that Social Media Marketing has a significant effect on Brand Awareness, Social Media Marketing has a significant effect on Brand Trust, Social Media Marketing has no significant effect on Purchase Intention, Brand Awareness has no significant effect on Purchase Intention, Brand Trust has a significant effect on Purchase Intention, Social Media Marketing has a significant effect on Purchase Intention through Brand Awareness, Social Media Marketing has a significant effect on Purchase Intention through Brand Trust.